2017
DOI: 10.48550/arxiv.1704.04216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of bulk viscosity and hadronic rescattering in heavy ion collisions at RHIC and LHC

Sangwook Ryu,
Jean-François Paquet,
Chun Shen
et al.

Abstract: We describe ultra-relativistic heavy ion collisions at RHIC and the LHC with a hybrid model using the IP-Glasma model for the earliest stage and viscous hydrodynamics and microscopic transport for the later stages of the collision. We demonstrate that within this framework the bulk viscosity of the plasma plays an important role in describing the experimentally observed radial flow and azimuthal anisotropy simultaneously. We further investigate the dependence of observables on the temperature below which we em… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Section IIB will describe the centrality selection procedure that is employed for this work, and section IIC will briefly introduce the details of the hydrodynamic and hadronic cascade simulations. The latter section will focus on the details of the implementations and the parameters used as the physics of these models has been discussed in great detail elsewhere [4,10]. The procedure of our flow analysis is explained in Section IID.…”
Section: Introductionmentioning
confidence: 99%
“…Section IIB will describe the centrality selection procedure that is employed for this work, and section IIC will briefly introduce the details of the hydrodynamic and hadronic cascade simulations. The latter section will focus on the details of the implementations and the parameters used as the physics of these models has been discussed in great detail elsewhere [4,10]. The procedure of our flow analysis is explained in Section IID.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of fluid-dynamical model calculations with experimental data, especially for the azimuthal structure of hadron spectra, have revealed that the ratios of shear and bulk viscosity to entropy density must be small in order to be consistent with the data [1][2][3][4][5][6][7]. The good agreement between fluid-dynamical models and experimental data is one of the strongest evidences that a small droplet of QGP is indeed formed in these collisions.…”
Section: Introductionmentioning
confidence: 67%
“…We will also look at how the transport coefficients, including the relaxation times, affect the viscous hydrodynamic results when computed in the small fixed mass approximation z 1 and dm/dT ≈ 0, without a mean field, which is commonly implemented in viscous hydrodynamic simulations. [78,81,82] A. Equilibrium initial conditions…”
Section: Bjorken Flowmentioning
confidence: 99%